Orthopaedic Rehabilitation Device Actuated with Pneumatic Muscles. (22nd July 2014) - Petre, Ioana; Deaconescu, Andrea; Rogozea, Liliana; Deaconescu, Tudor Ion
Year after year recovery clinics worldwide report significant numbers of lower limb bearing joint disabilities. An effective method for the speedy rehabilitation of patients with such afflictions is Continuous Passive Motion (CPM), drawing upon a range of specific equipment. This paper presents an innovative constructive solution for such orthopaedic rehabilitation equipment, designed to ensure a swift reintegration of patients at as low a cost as possible. The absolute novelty consists in the utilization of the linear pneumatic muscle as actuator of the orthopaedic rehabilitation equipment, thus achieving a light and highly compliant construction that satisfies safety requirements related to man-machine interaction. Pneumatic muscles are bio-inspired actuation systems characterized by a passive variable compliant behaviour. This property, deployed in rehabilitation systems, enables the development of human friendly devices, which are comfortable for the patients, and capable of safe interaction. This paper presents the constructive schematic of the orthopaedic rehabilitation equipment, the structure of the actuation and positioning system, and several of its functional characteristics.